2019
DOI: 10.2135/cropsci2018.09.0587
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Nutritive Value, Dung Quality, Decomposition, and Nutrient Movement into Soil in Smooth Bromegrass Pastures

Abstract: Legumes increase forage nutritive value in pastures; however, literature addressing the impacts on dietary nutritive value, dung quality, decomposition, and nutrient movement into soil remains scarce. Cattle grazing legume‐interseeded smooth bromegrass (Bromus inermis Leyss.) pastures may select diets with greater nutritive value and consequently produce dung that decomposes faster and increases nutrient movement into soil relative to cattle grazing N‐fertilized and unfertilized smooth bromegrass pastures. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 51 publications
(118 reference statements)
3
6
0
Order By: Relevance
“…Belowground transfer of biologically fixed N from legumes to non‐legumes has been described as a principal mechanism for the synergistic effect of legume‐grass mixtures on biomass yields (Frankow‐Lindberg & Dahlin, 2013). Increased nutritive value of cattle diets, return of N‐rich dung, and N movement into soil also has been observed in LEG pastures (Schick et al., 2019) and may have contributed to equivalent perennial grass biomass observed among main plots in our study.…”
Section: Resultssupporting
confidence: 78%
“…Belowground transfer of biologically fixed N from legumes to non‐legumes has been described as a principal mechanism for the synergistic effect of legume‐grass mixtures on biomass yields (Frankow‐Lindberg & Dahlin, 2013). Increased nutritive value of cattle diets, return of N‐rich dung, and N movement into soil also has been observed in LEG pastures (Schick et al., 2019) and may have contributed to equivalent perennial grass biomass observed among main plots in our study.…”
Section: Resultssupporting
confidence: 78%
“…The rye/clover pasture used in the present study was inter‐sown, and dung from this pasture source had a higher nitrogen content than the improved native‐ and forage oat‐derived dung (Table 2), as expected from previous legume‐based dung studies (e.g., Schick et al, 2019). Increasing grain concentration within feedlot diets increases nitrogen, phosphorus and water‐soluble ammonium (Hao et al, 2009); it can also affect pH and moisture content, which are limiting variables for brood production by dung beetles (Dadour & Cook, 1996).…”
Section: Discussionsupporting
confidence: 76%
“…The rye/clover pasture used in the present study was inter-sown, and dung from this pasture source had a higher nitrogen content than the improved native-and forage oat-derived dung (Table 2), as expected from previous legume-based dung studies (e.g., Schick et al, 2019).…”
Section: Dung Qualitysupporting
confidence: 76%
“…It produces tremendous growth in spring, particularly with N fertilizer inputs (Guretzky et al., 2013; Snell et al., 2014) but will go dormant in hot, dry summers (Casler & Kallenbach, 2007). Interseeding perennial legumes like alfalfa ( Medicago sativa L.), red clover ( Trifolium pratense L.), and birdsfoot trefoil ( Lotus corniculatus L.) would improve spatial and temporal distribution of forage (Harmoney et al., 2001) and dietary nutritive value (Schick et al., 2019), but dry soil conditions and grass competition often limits their establishment (Groya & Sheaffer, 1981; Guretzky et al., 2004). In this study, we observed that interseeding sorghum–sudangrass or sudangrass offers a strategy to consistently increase CP and IVOMD yields in late‐summer, though a tradeoff would be reduced CP concentrations (Table 6).…”
Section: Discussionmentioning
confidence: 99%